Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/10717544.2018.1464081
|View full text |Cite
|
Sign up to set email alerts
|

Modification of translationally controlled tumor protein-derived protein transduction domain for improved intranasal delivery of insulin

Abstract: Carrier peptides, termed protein transduction domains (PTDs), serve as provide promising vehicles for intranasal delivery of macromolecular drugs. A mutant PTD derived from human translationally controlled tumor protein (TCTP-PTD 13, MIIFRALISHKK) was reported to provide enhanced intranasal delivery of insulin. In this study, we tested whether its efficiency could be further improved by replacing amino acids in TCTP-PTD 13 or changing the amino acids in the carrier peptides from the l- to the d-form. We assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…In a previous study, we constructed single mutant, A6L of TCTP-PTD 13 and double mutant, A6L, I8A of TCTP-PTD 13 and designated TCTP-PTD 13M1 and TCTP-PTD 13M2, respectively and demonstrated that TCTP-PTD 13M2 was found to be a useful vehicle for the delivery of insulin through the nasal membrane (Bae et al., 2018 ). In this study, we additionally designed a substitution S9Y of TCTP-PTD 13M2, called TCTP-PTD 13M3 ( Table 1 ), because of its higher hydrophobicity than TCTP-PTD 13M2, might be better at cargo delivery than others.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study, we constructed single mutant, A6L of TCTP-PTD 13 and double mutant, A6L, I8A of TCTP-PTD 13 and designated TCTP-PTD 13M1 and TCTP-PTD 13M2, respectively and demonstrated that TCTP-PTD 13M2 was found to be a useful vehicle for the delivery of insulin through the nasal membrane (Bae et al., 2018 ). In this study, we additionally designed a substitution S9Y of TCTP-PTD 13M2, called TCTP-PTD 13M3 ( Table 1 ), because of its higher hydrophobicity than TCTP-PTD 13M2, might be better at cargo delivery than others.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the ability of TCTP-PTD analogs to increase the exendin-4 that delivered through the nasal administration, we performed PKs studies in normal rats. We studied using the simple mixtures and fixed their amounts based on our previous studies (Bae et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations